Innovation Capability and Knowledge Sharing: A Driving Model of Innovation Strategy - Mufti Agung Wibowo; Ari Siswati; Setya Indah; Widodo Widodo; Budhi Cahyono (Interdisciplinary Social Studies, 2025)
In today's dynamic and competitive business environment, organizations are constantly striving to enhance their innovation capabilities to maintain competitiveness. While innovation capability and knowledge sharing have been recognized as key factors, the role of innovation strategy as a moderating variable in the relationship between these two factors remains underexplored. This research aims to develop a model of the connection between innovation capability (IC), knowledge sharing (KS), and innovation strategy (IS), through a systematic literature review. This research employs a systematic literature review method, analyzing articles from Scopus and Web of Science databases published between 2003 and 2020. Content analysis was conducted on selected articles that met the inclusion criteria. The findings indicate that innovation strategy plays a moderating role in the relationship between innovation capability and knowledge sharing. The integration process between innovation variables and knowledge sharing has the potential to leverage enhancing innovation capability, which ultimately can improve organizational performance. The model developed in this study provides a theoretical contribution to understanding the mechanism of strengthening innovation capability through knowledge sharing practices moderated by innovation strategy. These findings also have practical implications for management in developing effective strategies to enhance organizational innovation capability.